Characterization of Nanocrystalline SiGe Thin Film Solar Cell with Double Graded-Dead Absorption Layer. (24th January 2012) - Wang, Chao-Chun; Wuu, Dong-Sing; Lien, Shui-Yang; Lin, Yang-Shih; Liu, Chueh-Yang; Hsu, Chia-Hsum; Chen, Chia-Fu
Abstract : The nanocrystalline silicon-germanium (nc-SiGe) thin films were deposited by high-frequency (27.12 MHz) plasma-enhanced chemical vapor deposition (HF-PECVD). The films were used in a silicon-based thin film solar cell with graded-dead absorption layer. The characterization of the nc-SiGe films are analyzed by scanning electron microscopy, UV-visible spectroscopy, and Fourier transform infrared absorption spectroscopy. The band gap of SiGe alloy can be adjusted between 0.8 and 1.7 eV by varying the gas ratio. For thin film solar cell application, using double graded-dead i-SiGe layers mainly leads to an increase in short-circuit current and therefore cell conversion efficiency. An initial conversion efficiency of 5.06% and the stabilized efficiency of 4.63% for an nc-SiGe solar cell were achieved.